STRATEGI PEMASARAN BERDASAR PADA SEGMENTASI DANPREFERENSI KONSUMEN TERHADAP JERUK LOKAL SERTA JERUK IMPOR - Hadia, Imelda; Syahrial, Ramon; Alimah, Siti; Kurniasari, Dwiyana Anella (Jurnal Agribisnis Wijaya Putra Surabaya, 2022)
Citrus fruit is one of the horticultural products that has a high volume of imports, causing local oranges to be slightly defeated. Consumer preferences for local and imported citrus fruits have differences, namely by using Chi-square analysis it is known that consumer preferences for local oranges are greenish yellow with a slightly sour sweet taste, medium fruit size, fresh aroma and have a moderate price. Imported oranges, there are differences in preferences on attributes other than color attributes, because consumers have the same opinion about the orange color in imported oranges. Market segmentation, based on the results of cluster research, has almost the same characteristics and shows that consumers of local and imported oranges are consumers who are still young around 1925 years old, female and male, who are graduates from high school or diploma and still have the status as students, unmarried and with incomes ranging from IDR 500,000 to IDR 2,499,999. The number of members in each family includes the number of small and medium members who usually buy oranges at Giant and Ramayana. Purchases are made erratically as much as 1-2 kg in one purchase.